Feeding the Mind: Humanitarianism and the Reconstruction of European Intellectual Life, 1919–1933 - Tomás Irish (Cambridge University Press, 2023)
Feeding the Mind explores how European intellectual life was rebuilt after the cataclysm of the First World War. Learned communities were left in ruins by the conflict and its consequences; cultural and educational sites were destroyed, writers and artists were killed in battle, and tens of thousands of others were displaced. Against the backdrop of an unprecedented post-war humanitarian crisis which threatened millions with starvation and disease, many organisations chose to focus on assisting intellectuals and their institutions, giving them food, medicine and books in order to stabilise European democracies and build a peaceful international order. Drawing on examples from Austria to Russia and Belgium to Serbia, Feeding the Mind analyses the role of humanitarianism in post-conflict reconstruction and explores why ideas and intellectuals were deemed to be worth protecting at a time of widespread crisis. This issue was pertinent in the century that followed and remains so today.